Tricuspid Valve Infective Endocarditis In Drug Abusers: Clinical Features and Results of Surgical Treatment - Lashmanov, DI; Bhandari, Krishna; Chiginev, VA; Pichugin, VV; Zemskova, EN (Nepalese Heart Journal, 2013)
The objective of this study was to evaluate the clinical features, diagnostic criteria and indications for surgery in patients – drug abusers with tricuspid valve infective endocarditis (TVIE), and outcome of surgical treatment in these patients. From December 1999 to August 2009 35 patients (drug addicts) with TVIE were operated in the department of acquired heart diseases of Cardiac and Vascular Surgery Center, Nizhny Novgorod. 25 males and 10 females aged from 15 to 51 years were included in this study. 3 patients were re-operated due to recurrence of endocarditis. Biological prosthetic valve "Bio-Lab" was used in all patients. Intravenous drug abuse was the cause of the disease in all patients. Acute onset with hectic fever, shivering, profuse sweating, intoxication and development of multi-organ failure were the main clinical features of the disease. Embolism of the peripheral branches of pulmonary artery by septic embolus or micro thrombi were common symptoms. Ultrasound investigation played an important role in diagnosis of TVIE. It was the only criteria for the verification of the diagnosis in patients with fever of unknown origin until the appearance of valve damages and cardiac murmurs. All 35 (100%) patients underwent tricuspid valve replacement (TVR). 3 (8.57%) patients underwent redo TVR because of prosthetic valve endocarditis due to persistent intravenous drug abuse after surgery. The hospital mortality rate was 0%. Acute debut of the disease may be the first clinical feature of tricuspid valve infective endocarditis in drug abusers. Ultrasound investigation is important for early diagnosis and effective treatment. Surgical treatment is indicated in cases of ineffective antibiotic therapy and massive tricuspid valve damages. Tricuspid valve replacement by a biological prosthesis was the treatment of choice in these patients. The use of biological prosthetic valve had good clinical results with low thrombogenic risk and high resistance to infection. Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 29-34 DOI: http://dx.doi.org/10.3126/njh.v7i1.8499